The groundwater flow velocity distribution in the urban areas: a case study - Alberti, Luca; Colombo, Loris; Francani, Vincenzo (Italian journal of engineering geology and environment, 2014)
This work involves the effects of the piezometric lowering due to the withdrawal of wells in urban areas, by examining in particular the case of milan (italy), whose drinking water wells are endowed with several hundred wells, pumping about 30 million cubic meters per year. An analysis performed by means of an hydrogeological model of the velocity field, showed that within the domain of the wide piezometric depression created by pumping wells, there are large areas of low flow velocity. these areas have been found both near the capture zone of the wells and where the capture zone of wells is very close, and it has been demonstrated that they have the effect of slowing the pollutants plume spreading downstream. A delimitation of the areas where the flow velocity drops below 50 m per year has been done. Moreover, a further study has dealt with the hydrochemistry of the city, demonstrating that the stagnation areas cause a renewal time increase, and they are often affected by a deterioration of the quality of water.